A study of factors affecting weight gain among tuberculosis patients under DOTS in district Amritsar - Sadana, Pooja; Kaur, Harpreet; Verma, Vishal (International Journal Of Community Medicine And Public Health, 2018)
Background: Wasting is a common feature in tuberculosis and treatment is aimed at achieving weight gain in pulmonary tuberculosis patients. The aims and objectives of the study were to study the extent of body weight gain during treatment and to identify the effect of different factors on weight gain among TB patients. Methods: The study was conducted on a total of 326 patients residing in the area of PHC Verka and registered with District Tuberculosis Centre, Amritsar. Weight change was assessed by taking the difference of weight at initial diagnosis and after completion of continuation phase therapy. Results: A total of 228 patients participated in the study. The mean (±SD) body weights (in kg) for the patients were 44.92±12.7 at diagnosis and 48.79±12.9 at the end of treatment. The mean (±SD) weight gain was 3.86±4.55 kgs at the end of treatment. The gain in weight at the end of treatment was associated with supervision of treatment and outcome of the TB patient. Conclusions: The findings showed that there is an association between gain in weight with supervision of treatment and outcome of the TB patient.